Therapeutic adherence and factors involved in young people and adults with problematic substance use - Giacinti, María (2019)
Introduction: The therapeutic adherence includes those behaviors of the subject that correspond to the recommendations agreed by the health professional. It is a complex phenomenon and determined by several factors. Objective: To analyze the therapeutic adherence and the factors involved, in young people and adults with problematic substance use, from the characterization of users and professionals. Methodology: Ex post-exploratory / descriptive study with mixed design. Two ad hoc questionnaires were applied, clinical histories and an observation grid were used. Participants were 31 users and 6 professionals (psychologists and psychiatrists) of both sexes from a private psychiatric institution. Results:The majority of users adhere to the treatment, especially those of male sex, from 41 to 50 years old, single and with full secondary. They presented social support, economic resources to carry out the treatment, active labor situation and where the popular belief about the consumption did not affect the treatment. In turn, he had a history of previous treatments and had psychiatric comorbidity. This agrees with that expressed by psychiatrists, male, aged between 36 and 40 years. Discussion: In the sample investigated, according to the characterization of users and professionals, the majority of users adhered to the treatment.